2019
DOI: 10.3390/app9245360
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap Analysis of the Production Processes Capability Assessment

Abstract: The high customer requirements for appropriate product quality pose a challenge for manufacturers and suppliers and also cause them many problems related to ensuring a sufficiently high product quality throughout the entire production cycle. For the above reasons, it is so important to assess the capability of monitored processes, and shaping, analyzing and controlling the capability of processes is an important aspect of managing an organization that uses a process approach to management. The use of an approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Since ̂ is a point estimate obtained from sample data, it is necessary to construct confidence interval (CI) of the capability index for inference purpose, especially when the sample size is relatively small. In literature, many works (Chou et al, 1990;Zhang et al, 1990;Kushler and Hurley, 1992;Nagata, 1991;Nagata and Nagahata, 1994;Peng, 2010;Stoma et al, 2019) are reported on the construction of confidence intervals of estimated capability indices. But all these works assume that quality characteristic of interest follows normal distribution.…”
Section: Estimation Of Confidence Interval Of ̂mentioning
confidence: 99%
“…Since ̂ is a point estimate obtained from sample data, it is necessary to construct confidence interval (CI) of the capability index for inference purpose, especially when the sample size is relatively small. In literature, many works (Chou et al, 1990;Zhang et al, 1990;Kushler and Hurley, 1992;Nagata, 1991;Nagata and Nagahata, 1994;Peng, 2010;Stoma et al, 2019) are reported on the construction of confidence intervals of estimated capability indices. But all these works assume that quality characteristic of interest follows normal distribution.…”
Section: Estimation Of Confidence Interval Of ̂mentioning
confidence: 99%
“…The assessment criteria of process capabilityis shown in Table 4. 44, 45 As can be seen, when C p < 0 . 67 and 0 . 67 < C p < 1 . 0 , the process capability is insufficient, thus failing to meet the technical requirements of quality. And when C p > 1 . 67 , the process capability is surplus, thus causing unnecessary manufacturing cost for enterprises.…”
Section: Example Verificationmentioning
confidence: 99%
“…The low stiffness of such parts, which is lower than the stiffness of the machine tool, can (under certain conditions) cause vibrations and the occurrence of factors that disrupt and destabilize the machining process [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%